Possible effect of genetic background in thrombophilia genes on clinical severity of patients with coronavirus disease-2019: A prospective cohort study - Ozlem Sezer; Ozgur Gunal; Recai Aci; Adem Keskin (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background and objective: Thrombotic and microangiopathic effects have been reported in Coronavirus Disease-2019 (COVID-19) patients. In the present study, we aimed to examine the relationship between hereditary thrombophilia factors and the clinical picture severity of COVID-19 patients.